A Systematic Literature Review on The Development and Evaluation of Honeydew Pectin with Aloe Vera as Edible Coating - Rudi, Muhamad Azri (Progress in Engineering Application and Technology, 2021)
The biggest problem encountered by the food manufacturer is the loss of quality of food products during storage. Although there are natural, edible wax coating on the market right now, the risk of a person getting intestine and colon cancer are noticeable high because the coating itself is not easily digestible. The main objective of this study is to investigate the different methods and composition of coating film formation. Three configurations of edible films can be produced mainly by pectin of honeydew melon as the basic structure. The other two variants are by combining the pectin with 100% of Aloe Vera extract. All three of them would be applied to the papaya fruit by using a wet method, which is simple dipping and spraying the pectin solution on the surface and cross section of the papaya fruit. Pectin coated fruits should be able to reduce loss in weight while maintaining high soluble solid concentration without affecting its pH, Titrate acidity (TA), ascorbic acid (AA) and antioxidant activities as compared to uncoated papaya fruit that decayed within 15 days of ambient room temperature storage